Ways of Fund Market Development in Uzbekistan - Sherali Sultonov Nuraliyevich; Nodira Soatova Bobokhanovna (Genius Publishing Group, 2022)
The article analyzes the scientific views of foreign economists on the essence, features, scientific and theoretical issues of the stock market, as well as indicators of the stock market of Uzbekistan. The authors have formed their own opinions, scientific and theoretical conclusions and suggestions on the further improvement of the stock market of Uzbekistan.
Keywords: Stock Market; Loan Capital; Securities; Market